Comparative genomic analyses of aerobic planctomycetes isolated from the deep sea and the ocean surface - Lise Øvreås; Nicolai Kallscheuer; Rita Calisto; Nicola Bordin; Julia E. Storesund; Christian Jogler; Damien Devos; Olga Lage (Antonie van Leeuwenhoek, 2025)
On the deep and dark seafloor, a cryptic and yet untapped microbial diversity flourishes around hydrothermal vent systems. This remote environment of difficult accessibility exhibits extreme conditions, including high pressure, steep temperature- and redox gradients, limited availability of oxygen and complete darkness. In this study, we analysed the genomes of three aerobic strains belonging to the phylum Planctomycetota that were isolated from two deep-sea iron- rich hydroxide deposits with low temperature diffusive vents. The vents are located in the Arctic and Pacific Ocean at a depth of 600 and 1,734 m below sea level, respectively. The isolated strains Pr1d T , K2D and TBK1r were analyzed with a focus on genome-encoded features that allow phenotypical adaptations to the low temperature iron-rich deep-sea environment. The comparison with genomes of closely related surface-inhabiting counterparts indicates that the deep-sea isolates do not differ significantly from members of the phylum Planctomycetota inhabiting other habitats, such as macroalgae biofilms and the ocean surface waters. Despite inhabiting extreme environments, our “deep and dark”-strains revealed a mostly non-extreme genome biology.

Benefits of protected areas for nonbreeding waterbirds adjusting their distributions under climate warming - Elie Gaget; Diego Pavón‐Jordán; Alison Johnston; Aleksi Lehikoinen; Wesley M. Hochachka; Brett K. Sandercock; Alaaeldin Soultan; Hichem Azafzaf; Nadjiba Bendjedda; Taulant Bino; Luka Božič; Preben Clausen; et al. (Conservation Biology, 2021)
Climate warming is driving changes in species distributions and community composition. Many species have a so‐called climatic debt, that is, shifts in range lag behind shifts in temperature isoclines. Inside protected areas (PAs), community changes in response to climate warming can be facilitated by greater colonization rates by warm‐dwelling species, but also mitigated by lowering extirpation rates of cold‐dwelling species. An evaluation of the relative importance of colonization‐extirpation processes is important to inform conservation strategies that aim for both climate debt reduction and species conservation. We assessed the colonization‐extirpation dynamics involved in community changes in response to climate inside and outside PAs. To do so, we used 25 years of occurrence data of nonbreeding waterbirds in the western Palearctic (97 species, 7071 sites, 39 countries, 1993–2017). We used a community temperature index (CTI) framework based on species thermal affinities to investigate species turnover induced by temperature increase. We determined whether thermal community adjustment was associated with colonization by warm‐dwelling species or extirpation of cold‐dwelling species by modeling change in standard deviation of the CTI (CTI SD ). Using linear mixed‐effects models, we investigated whether communities in PAs had lower climatic debt and different patterns of community change than communities outside PAs. For CTI and CTI SD combined, communities inside PAs had more species, higher colonization, lower extirpation, and lower climatic debt (16%) than communities outside PAs. Thus, our results suggest that PAs facilitate 2 independent processes that shape community dynamics and maintain biodiversity. The community adjustment was, however, not sufficiently fast to keep pace with the large temperature increases in the central and northeastern western Palearctic. Our results underline the potential of combining CTI and CTI SD metrics to improve understanding of the colonization‐extirpation patterns driven by climate warming.

Topographic distribution of brain iron deposition and small cerebrovascular lesions in amyotrophic lateral sclerosis and in frontotemporal lobar degeneration: a post-mortem 7.0-tesla magnetic resonance imaging study with neuropathological correlates - Jacques De Reuck; David Devos; Caroline Moreau; Florent Auger; Nicolas Durieux; Vincent Deramecourt; Florence Pasquier; Claude-Alain Maurage; Charlotte Cordonnier; Didier Leys; Regis Bordet (Acta Neurologica Belgica, 2017)

Origin and fate of the single‐island endemic moss Orthotrichum handiense - Jairo Patiño; Rafael Medina; Alain Vanderpoorten; Juana M. González‐Mancebo; Olaf Werner; Nicolas Devos; Rubén G. Mateo; Francisco Lara; Rosa M. Ros (Journal of Biogeography, 2013)
Aim Our aims were: to determine the evolutionary origin of the single‐island endemic moss Orthotrichum handiense ; to assess whether its endemicity results from a recent origin or founder event, a loss of dispersal ability, specific habitat requirements, or contraction of a formerly wider range; and to make predictions about its ability to face ongoing climate change. Location Fuerteventura, Canary Islands. Methods The evolutionary origin of O. handiense was determined by phylogenetic analysis and molecular dating. The spatial genetic structure and demographic history of 48 individuals of O. handiense were analysed with inter‐simple sequence repeat ( ISSR ) markers through analyses of molecular variance, Mantel tests, mismatch distributions and bottleneck analyses. The macroclimatic envelope of the species was modelled using an ensemble approach of eight species distribution models, and its suitable areas predicted for extant, past (21 ka) and future (2050, 2080) conditions. Results Orthotrichum handiense was resolved as sister to the Californian O . underwoodii and their most recent common ancestor was dated to early Miocene–Pliocene. ISSR analyses revealed extremely low levels of genetic diversity and provided evidence for a recent bottleneck and for isolation‐by‐distance at the local scale. The different models investigated all pointed to the mismatch between the limited extant distribution and the extent of macroclimatically suitable areas. All models predicted climatic unsuitability on Fuerteventura and Lanzarote at 21 ka, but were conflicting in other areas. A dramatic reduction and loss of suitable areas were predicted for 2050 and 2080, respectively. Main conclusions The phylogenetic position of O. handiense points to a long‐distance dispersal event from a western North American ancestor and emphasizes the differences in the origin of Macaronesian endemic bryophytes and angiosperms. The predicted absence of suitable macroclimatic conditions in Fuerteventura at 21 ka supports the hypothesis of a palaeoendemic origin and a recent founder event in Fuerteventura, consistent with the low levels of genetic diversity and with evidence for a recent bottleneck. While the biogeographical history of the species hence involves major dispersal events over periods of tens of thousands of years, its ability to respond quickly to predicted climate change during the next few decades is questioned.

The barriers to oceanic island radiation in bryophytes: insights from the phylogeography of the moss Grimmia montana - Alain Vanderpoorten; Nicolas Devos; Bernard Goffinet; Olivier J. Hardy; A. Jonathan Shaw (Journal of Biogeography, 2008)
Aim In contrast to angiosperms, bryophytes do not appear to have radiated in Macaronesia and the western Mediterranean. We evaluate if: (1) the apparent lack of radiation in bryophytes reflects our failure to recognize cryptic endemic species; (2) bryophytes are characterized by extremely low evolutionary rates; or (3) bryophytes have a high dispersal ability, which prevents genetic isolation. Location Worldwide, with a special emphasis on Macaronesia and the western Mediterranean. Methods Three chloroplast regions were sequenced from samples of the moss Grimmia montana from its entire distribution range. Network analyses, Fst and Nst statistics were used to describe and interpret the phylogeographical signal in the data. Results Despite significant phylogeographical signal in the chloroplast genome, which demonstrates limits to gene flow at the continental scale, repeated sister group relationships observed among accessions from different geographical areas suggest recurrent colonization patterns. These observations are consistent with mounting evidence that intercontinental distributions exhibited by many bryophyte species result from long‐distance dispersal rather than continental drift. Madeiran and western Mediterranean island haplotypes are either shared by, or closely related to, European and North American ones. Fst values between Madeira, western Mediterranean islands, North America and Europe are not significantly different from zero, and suggest that Madeira and the south‐western Mediterranean are subject to strong transatlantic gene flow. By contrast, haplotypes found in the Canary Islands are shared or closely related to those of populations from south‐western Europe or southern Africa. Main conclusions Multiple origins and colonization events are not consistent with the hypothesis of a relictual origin of the Macaronesian moss flora. One possible reason for the failure of taxa that experienced multiple colonization events to radiate is niche pre‐emption. We suggest that strong gene flow, coupled with the occupancy of all suitable niches, either by earlier conspecific colonizers or by other species, could be the mechanism preventing island radiation in G. montana and other cryptogams with high long‐distance dispersal abilities.